In Vitro Evaluation of Rice and Maize Gluten Meals in the Concentrate Mixture of Ruminants - Mahesh, M.S. (Indian Journal of Animal Nutrition, 2021)
Concentrate mixtures formulated to contain graded levels (25, 50, 75 and 100%) of rice gluten meal (RGM) and maize gluten meal (MGM), isonitrogenously replacing groundnut cake (GNC) were evaluated for chemical composition, protein fractions, in vitro gas production and rumen fermentation characteristics. The concentrate mixtures contained an average of 22.1% crude protein (CP). The range of values obtained for various CNCPS protein fractions (% CP) was: 6.9-8.9, 12.7-24.1, 46.3-55.1, 15.3-17.6, 5.4-11.1 for A, B1, B2, B3 and C, respectively across various treatments. Furthermore, rumen undegradable protein was maximum (P